Seasonal influence on testicular function of male raccoons, Procyon lotor - Kaneko, K.(Azabu Univ., Sagamihara, Kanagawa (Japan). School of Veterinary Medicine); Akiya, Y; Sato, H; Tanaka, A; Aoki, H; Miyoshi, M; Abukawa, T; Mochizuki, M; Kawakami, S (Journal of Reproduction and Development, 2005)
In order to clarify the breeding capability of male raccoons in Japan, the testes of raccoons, a nuisance animal, collected in Kanagawa Prefecture and Hokkaido were histologically inspected. Furthermore, testosterone concentrations in their blood were measured. The testosterone concentrations increased in winter and the diameter of seminiferous tubules and the spermatogenetic score decreased in summer for the animals captured in Kanagawa Prefecture. For the animals captured in Hokkaido, the diameter of seminiferous tubules did not change and the decrease of the spermatogenetic score in summer was slight. As the above results show, there is a breeding season in male raccoons in Japan, and the reduction of testicular function in summer was greater in animals captured in Kanagawa Prefecture than in animals captured in Hokkaido.